Current knowledge on the Ralstonia solanacearum type III secretion system. Issue 6 (26th April 2013) - Coll, Núria S.; Valls, Marc
<x xml:space="preserve">Abstract</x> This article exhaustively reviews current knowledge on the type III as the main virulence determinant of R. solanacearum. Recent findings on this topic are interpreted in the plant‐pathogen research context and future research directions are proposed.